The professional and ethical potential of Lithuanian property valuers - Galiniene, Birute; Marčinskas, Albinas; Deveikis, Steponas (International Journal of Strategic Property Management, 2010)
Lithuania is a small developing market economy which inherited the specific soviet economic structure and so‐called “homus sovieticus” mentality which excluded a possibility for business of property valuation. Within a historically short period of time Lithuania moved from the closed soviet economic area into the area of global economy, which presented different business valuation criteria. Taking the above into account, let us evaluate the professional and ethical potential of Lithuanian property valuers, who have played and will be playing a significant role in the country’s economic development, and see whether this potential will enable them to become full‐fledged members of the Western property valuers’ community. First Published Online: 18 Oct 2010